Early Diagnosis of Gallbladder Carcinoma: An Algorithm Approach. (18th October 2012) - Vijayakumar, Abhishek; Vijayakumar, Avinash; Patil, Vijayraj; Mallikarjuna, M. N.; Shivaswamy, B. S.
Abstract : Gall bladder carcinoma is the most common biliary tract cancer. Delayed presentation and early spread of tumor make it one of the lethal tumors with poor prognosis. Considering that simple cholecystectomy for T1 disease could offer a potential cure, it is increasingly needed to identify it at early stages. Identification of high-risk cases and offering prophylactic cholecystectomy can decrease the incidence of gallbladder carcinoma. With advances in diagnostic tools like contrast-enhanced endoscopic ultrasound, elastography, multidetctor CT, MRI, and PET scan, we can potentially diagnose gallbladder carcinoma at early stages. This paper reviews the various diagnostic modalities available and an algorithmic approach to early diagnosis of gallbladder carcinoma.